Effect of resistance training on satellite cells in old mice – a transcriptome study: implications for sarcopenia. Issue 2 (22nd February 2022) - Hsu, Wei-Bin; Lin, Shih-Jie; Hung, Ji-Shiuan; Chen, Mei-Hsin; Lin, Che-Yi; Hsu, Wei-Hsiu; Hsu, Wen-Wei Robert
Abstract : Aims: The decrease in the number of satellite cells (SCs), contributing to myofibre formation and reconstitution, and their proliferative capacity, leads to muscle loss, a condition known as sarcopenia. Resistance training can prevent muscle loss; however, the underlying mechanisms of resistance training effects on SCs are not well understood. We therefore conducted a comprehensive transcriptome analysis of SCs in a mouse model. Methods: We compared the differentially expressed genes of SCs in young mice (eight weeks old), middle-aged (48-week-old) mice with resistance training intervention (MID+ T), and mice without exercise (MID) using next-generation sequencing and bioinformatics. Results: After the bioinformatic analysis, the PI3K-Akt signalling pathway and the regulation of actin cytoskeleton in particular were highlighted among the top ten pathways with the most differentially expressed genes involved in the young/MID and MID+ T/MID groups. The expression of Gng5, Atf2, and Rtor in the PI3K-Akt signalling pathway was higher in the young and MID+ T groups compared with the MID group. Similarly, Limk1, Arhgef12, and Araf in the regulation of the actin cytoskeleton pathway had a similar bias. Moreover, the protein expression profiles of Atf2, Rptor, and Ccnd3 in each group were paralleled with the results of NGS. Conclusion: Our results revealed that age-induced muscle loss might result from age-influenced genes that contribute to muscle development in SCs. After resistance training, age-impaired genes were reactivated, and age-induced genes were depressed. The change fold in these genes in the young/MID mice resembled those in the MID + T/MID group, suggesting that resistance training can rejuvenate the self-renewing ability of SCs by recovering age-influenced genes to prevent sarcopenia. Cite this article: Bone Joint Res 2022;11(2):121–133.